A novel Enterococcus faecium phage EF-M80: unveiling the effects of hydrogel-encapsulated phage on wound infection healing - Khazani Asforooshani, Mahshid; Elikaei, Ameneh; Abed, Sahar; Shafiei, Morvarid; Barzi, Seyed Mahmoud; Solgi, Hamid; Badmasti, Farzad; Sohrabi, Aria (Frontiers in Microbiology, 2024)
Background Enterococcus faecium is one of the members of ESKAPE pathogens. Due to its resistance to antimicrobial agents, treating this bacterium has become challenging. The development of innovative approaches to combat antibiotic resistance is necessary. Phage therapy has emerged as a promising method for curing antibiotic-resistant bacteria. Methods In this study, E. faecium phages were isolated from wastewater. Phage properties were characterized through in vitro assays (e.g. morphological studies, and physicochemical properties). In addition, whole genome sequencing was performed. A hydrogel-based encapsulated phage was obtained and its structure characteristics were evaluated. Wound healing activity of the hydrogel-based phage was assessed in a wound mice model. Results The purified phage showed remarkable properties including broad host range, tolerance to high temperature and pH and biofilm degradation feature as a stable and reliable therapeutic agent. Whole genome sequencing revealed that the genome of the EF-M80 phage had a length of 40,434 bp and harbored 65 open reading frames (ORFs) with a GC content of 34.9% (GenBank accession number is OR767211). Hydrogel-based encapsulated phage represented an optimized structure. Phage-loaded hydrogel-treated mice showed that the counting of neutrophils, fibroblasts, blood vessels, hair follicles and percentage of collagen growth were in favor of the wound healing process in the mice model. Conclusion These findings collectively suggest the promising capability of this phage-based therapeutic strategy for the treatment of infections associated with the antibiotic-resistant E. faecium. In the near future, we hope to expect the presence of bacteriophages in the list of antibacterial compounds used in the clinical settings.